(untitled) (Praxis Educativa, 2018)
In this work a set of notes that aim to dialogue with some of the questions left by the authors of the Manifesto are presented. Our reflective journey starts from considering that the demand formulated by Biesta and Säfström implies returning to a questioning mode that addresses the ontology of education as a nodal issue for educational theory and research. Our proposal focuses on investigating the tensions produced by addressing the signifiers of education from another epistemic record. Based on the episteme of the Human Sciences, topics that support the idea that education has its place in the cultural field are developed and that it acquires meaning as it generates and produces the process of humanization. Speaking in the name of education in an educational way requires overcoming binarism to enable thinking in paradoxical and complex terms.